Compressive behaviour and microstructures of concrete incorporating pretreated recycled powder/aggregates: The coupling effects of calcination and carbonization. (1st June 2023) - Zhang, Baifa; Feng, Yuan; Xie, Jianhe; Chen, Wei; Xue, Zixin; Zhao, Gexiao; Li, Yun; Li, Jianglin; Yang, Jian
Abstract: The incorporation of recycled powder (RP), recycled fine aggregate (RFA), and recycled coarse aggregate (RCA) can adversely affect the performance of cement-based materials. In this study, RP, RFA, and RCA (with or without pretreatment) are used to replace cement, natural fine aggregate (NFA), and natural coarse aggregate (NCA), respectively, to prepare recycled concrete (RC). With an increase in the replacement ratio of recycled materials, the mechanical properties of recycled cement paste (RCP), recycled mortar (RM), and RC are found to gradually decrease. Pretreatment (calcination and carbonization) of recycled materials favours the improvement of their physical and chemical properties, in which the coupling pretreatment of calcination and carbonization is found to lead to the best improvement in material properties. Among the RCs containing 50% RCA, the RCA carbonized for 24 h after calcination at 400 °C favours the best performance improvement for RC, with the compressive strength, elastic modulus, and compressive toughness increased by 35.8%, 19.3%, and 39.9%, respectively. The coupling effect of pretreatment results in the bonding between the matrix and RCA becoming closer, accompanied by an effective improvement in the ITZ. However, a too high calcination temperature (>600 °C) will negatively affect the performance of RC, whereas carbonization for a prolonged period of time barely alters the performance of RC. These results indicate that the coupling pretreatment of recycled materials favours the properties of the as-obtained RC, and calcination at 400 °C with carbonization at 6 h is the optimal pretreatment for recycled materials in terms of economic value and mechanical properties. Highlights: The coupling effect of calcination and carbonization pretreatment is investigated. The axial stress-strain behaviour of RC containing various recycled materials is studied. The coupling pretreatment can increase the compressive strength of RC by 35.8%.